Dynamics of Corynespora leaf fall and Colletotrichum leaf spot diseases of rubber plants (Hevea brasiliensis) - Manju M J; Benagi V I; Jacob C K; Shankarappa T H; Vinod K K (Journal of Mycology and Plant Pathology, 2014)
A field study was carried out to understand the dynamic nature of two major leaf diseases, Corynespora leaf fall (CLF) and Colletotrichum leaf spot (CLS) of rubber plants (Hevea brasiliensis). These diseases appeared regularly in the rubber plantations and caused more damages to younger leaves. Fresh infection of CLF disease was observed in the plantation from the second fortnight of January during the period of refoliation and the disease intensity was maximum from the second fortnight of March to the first fortnight of April. The disease decreased considerably after the onset of rains and remained mild until the next reflushing season. The disease decreased considerably after the onset of rains and remained mild until the next reflushing season. The disease intensity was limited to refoliation period after the annual wintering and warm humid periods only. The CLS disease was present throughout the year in the plantation at all the stages of leaves. However, the disease intensity was mainly confined to younger plantations. The disease was found to establish with the refoliation and became more severe during the rainy season and warm humid months. Unlike CLF, this disease dis not cause considerable economic damage to mature rubber, but it is a serious problems in nurseries and for very young rubber plants in the main field.
Source Year: 2014
Keywords: Colletotrichum leaf spot; Corynespora leaf fall; Rubber plants